(untitled) - Segal, Margaret Keenan (New York, 1990)
Interactions One: A Writing Process Book, 2/e, is designed to lead students through the writing process and provide an assortment of activities to help them master the wide variety of skills necessary for good writing. Ideal for low-intermediate to intermediate students.
Keywords: English language,Tiếng Anh; Study and teaching,Dạy và học